Murach's Java servlets and JSP : training & reference - Murach, Joel; Steelman, Andrea (Mike Murach & Associates, 2008)
This new edition of Murach\'s Java Servlets and JSP makes it easier than ever for Java developers to master web programming. It starts by showing how to install and use Tomcat as a web server and NetBeans as an IDE. Then, it teaches how and when to use JavaServer Pages and Java servlets to build well-structured web applications that implement the MVC pattern. Next, it shows how to use sessions, cookies, JavaBeans, Expression Language (EL), the JSP Standard Tag Library (JSTL), and custom tags. Then, it shows how to use JDBC and connection pooling to work with a MySQL database. Finally, it shows how to use JavaMail, SSL/TLS, authentication, listeners, and filters. These are the skills that you need to build professional Java web applications. A great read for any Java developer.
Keywords: Informatics; knihovnictví, informační věda a muzeologie; JavaServer pages; informatika; programovací jazyk; Programming Languages